2020
DOI: 10.1002/mgg3.1557
|View full text |Cite
|
Sign up to set email alerts
|

A competing endogenous RNA network reveals key lncRNAs associated with sepsis

Abstract: The initial definitions, that sepsis is caused by a host's systemic inflammatory response syndrome (SIRS) to infection,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The results showed that reactome biological oxidations, inflammasomes, cytokine-cytokine receptor interaction, toll-like receptor signaling pathway, JAK/STAT signaling pathway, and NF-κB activation were differentially enriched in the high-expression LINC00963 phenotype of CESC. Furthermore, LINC00963 could be associated with cellular function, such as biological oxidations and inflammasomes, in addition to immune regulation and cancer progression [ 21 23 ]. Protective immune toll-like receptors can induce the secretion of inflammatory cytokines and induce lymphocytes to mediate an adaptive antigen-specific immune response for eliminating invasive microorganisms [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that reactome biological oxidations, inflammasomes, cytokine-cytokine receptor interaction, toll-like receptor signaling pathway, JAK/STAT signaling pathway, and NF-κB activation were differentially enriched in the high-expression LINC00963 phenotype of CESC. Furthermore, LINC00963 could be associated with cellular function, such as biological oxidations and inflammasomes, in addition to immune regulation and cancer progression [ 21 23 ]. Protective immune toll-like receptors can induce the secretion of inflammatory cytokines and induce lymphocytes to mediate an adaptive antigen-specific immune response for eliminating invasive microorganisms [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using microarray and whole genomic transcription sequencing with bioinformatics analyses on blood samples from patients with sepsis discovered 46 differentially expressed lncRNAs (DElncRNAs) ( 21 ). Additionally, 28 upregulated and 61 downregulated lncRNAs were identified in the public reported NCBI GEO dataset ( 22 ).…”
Section: The Association Between Lncrnas and Sicdmentioning
confidence: 99%
“…As previously discussed, numerous lncRNAs are aberrantly expressed in SICD compared with normal cardiac tissue or cell lines, and this is useful to distinguish SICD patients from healthy cohorts. Although nearly all lncRNAs with direct evidence of their involvement in SICD were declared as potential biomarkers of SICD, those lncRNAs also show aberrant expression patterns in sepsis without cardiac dysfunction, especially critical patients, and in other non-sepsis situations such as MI, I/R, and acute kidney injury ( 21 , 22 , 24 , 26 , 110 , 114 , 148 ). This reduces the reliability of using these lncRNAs as potential biomarkers of SICD.…”
Section: Lncrnas As Biomarkers and Therapeutic Targetsmentioning
confidence: 99%